Methods for studying rodent intestinal lipoprotein production and metabolism - Kohan, Alison B. (2012)
Lipid absorption begins with the digestion of dietary triacylglycerol and ultimately results in the secretion of triacylglycerol in chylomicrons into the lymphatics. Additionally, the intestine also secretes numerous proteins and peptides involved in lipid and lipoprotein metabolism in response to food. Ultimately, chylomicrons and these proteins, peptides, and hormones are found in lymph. The lymph fistula rat model has traditionally been used to study this intestinal absorption of nutrients, especially lipids, but recently, this model has also been used for studying the secretion of hormones by the small intestine. The protocols described in this article include the lymph fistula rat and mouse model, as well as in vivo chylomicron metabolism studies. These experimental models are helpful for the study of metabolic phenotypes, the characterization of intestinal lipid absorption and transport, and determining peripheral metabolism of intestinally derived lipoproteins.